2015
DOI: 10.1017/dmp.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Do Shared Barriers When Reporting to Work During an Influenza Pandemic Influence Hospital Workers’ Willingness to Work? A Multilevel Framework

Abstract: Hospital administrators should consider the implications of barriers and areas of residence on the disaster response capacity of their workforce. Our findings underscore communication and development of preparedness plans to improve the resilience of hospital workers to mitigate absenteeism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…A number of personal, institutional, and behavioral factors were found to be associated with the willingness of physicians to work during the COVID-19 pandemic. Younger physicians participating in our study were more likely to report to their willingness to work during the pandemic, which is similar to the finding of a previous study conducted in the USA [35], though some other studies found that age was not a significant factor of willingness to work [20,36,37]. Having multiple comorbidities makes senior physicians more vulnerable to the…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A number of personal, institutional, and behavioral factors were found to be associated with the willingness of physicians to work during the COVID-19 pandemic. Younger physicians participating in our study were more likely to report to their willingness to work during the pandemic, which is similar to the finding of a previous study conducted in the USA [35], though some other studies found that age was not a significant factor of willingness to work [20,36,37]. Having multiple comorbidities makes senior physicians more vulnerable to the…”
Section: Discussionsupporting
confidence: 87%
“…Though the practice of using adequate PPE or the availability of that equipment in their workplace was not associated with their willingness to work, high self-reported compliance to the recommended PPE was a predictor of that. Risk perception is an important factor to influence the HCWs' decision to report to their job, as found both in our study and the previous ones [20,21,[35][36][37]. Higher perceived risk makes them reluctant to continue their job.…”
Section: Plos Onesupporting
confidence: 71%
“…Due to their full-time status, such HCWs are more likely to be placed on response teams, which can enhance feelings of stress and perception that participation in the work is mandatory. As an infectious disease outbreak can result in decreased willingness to work [29][30][31][32][33], compulsory work may exacerbate negative impacts on psychological well-being in that con icts between work obligations and worry about infection can affect mental wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…13 The plan should limit the need of health care workers to function in variance to their routine environment and positions. 15,14 Inadequate policies increase vulnerability to adverse effects, 8,11 negatively impact the staff, and amplify the risk of their being unavailable to report for duty when activated. 13,15…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Perceived emergency preparedness of the workplace influences the readiness of health care workers to report to duty. [13][14][15] More so, it impacts additional vital aspects of emergency response, such as adherence to protection regulations or directives issued by governing authorities. 16 Think-tanks are effective in designing policies and enhancing governance capacities in private and public sectors, and their use has grown and intensified.…”
mentioning
confidence: 99%